(untitled) (Annals of Medicine and Medical Sciences, 2025)
Patient recruitment and retention remain persistent challenges in oncology clinical trials, often leading to delays, increased costs and compromised data validity. Traditional recruitment strategies frequently fail to identify suitable participants efficiently which may result in under-enrollment and high dropout rates that limit the generalizability of trial outcomes. This paper examines how the use of artificial intelligence (AI) and mobile technologies affect patient recruitment and retention in oncology clinical trials. Employing a retrospective analysis of adult oncology trials conducted in the United States between 2017 and 2021, the study utilizes data from adult clinical trial registries to evaluate recruitment patterns and outcomes. Findings demonstrate that AI and mobile health (mHealth) tools can significantly streamline recruitment processes, reduce participant attrition and enhance overall trial efficiency. Integrating these technologies into clinical research operations may aid oncology trials to achieve more reliable data, accelerate therapeutic discoveries and ultimately contribute to improved cancer care outcomes. The study concludes that the integration of AI and mobile health technologies will not only improve operational efficiency but also help address disparities in participation, particularly among underrepresented groups. Therefore, this study recommends that clinical trial administrators should adopt AI and mobile health (mHealth) tools for patient matching, recruitment optimization and retention tracking.